Investor sentiment and bank deposits in Malaysia: do bank managers Time the Market while pricing deposits? - Fauzias Mat Nor; Mamunur Rashid; Izani Ibrahim; Bai Vunyi (Penerbit Universiti Kebangsaan Malaysia, 2014)
Financial market activities increase during high sentiment in Malaysia. Overly optimistic behavior is one of the reasons behind the escalation which influences flows of deposit to commercial banks. This study discusses the influence of investor sentiment on bank deposits and investigates any potential causal relationships among deposits, sentiment and other fundamental variables. An investor sentiment index is constructed using two - attitude based sentiment proxies, namely consumer sentiment index and business condition index, the Bursa Malaysia stock market turnover, and the ASEAN ITSE composite index. The VECM test found the sentiment index to positively influence deposit flows in banks in Malaysia in the long run. Partial short run significance was revealed from the first lag of sentiment proxies, which was positive as well. Among other variables, output (GOP), money supply and interest rate showed a positive long-run relationship on bank deposits whereas currency did have a negative impact on deposits. Output (GDP), money supply and sentiment Granger caused bank deposits, whereas deposits and interest rate showed bi-directional causal relationships. The study lends support to the argumentthat higher sentiment increases stock and bank market activities primarily when the financial market is bank dependent. Bi-directional causal relationships signifythat the conventional demand-supply mechanism is active in pricing deposits. Banks set higher interest rates to attract large amounts of deposits during a low sentiment period and vice versa. Similarly, banks can offer a low interest rate on deposits during a high sentiment period assuming that deposits will automatically flow though the banking channel in a bank-dependent financial market. This argument connotes the presence of timing effect in deposit pricing within the bank financial market.